Buoyant particulate strategy for few-to-single particle-based plasmonic enhanced nanosensors - Dongjie Zhang (Nature Portfolio, 2020)
Plasmonic-enhanced nanosensors are limited in practical applications, as it remains challenging to detect molecules at low concentrations. Here, the authors introduce a buoyant particulate strategy in order to enrich analytes in the plasmonic hot spots.